1964, das Jahr, mit dem "68" begann - Lorenz, Robert; Walter, Franz (2014)
The year 1968 is commonly connected with the upending of traditional social structures and the entrance of civil rights progress. However, this date was not the starting point but rather the point of culmination for political and social change, for much of what connects with the significant year of 1968 has earlier roots. The year 1964 was witness to numerous events in a turning point that heralded the coming social upheaval. With reference to different social and political episodes This volume questions the commonly recognized significance of 1968 and demonstrates, that a significant proportion of mental modernization took place much earlier.